The Role of Nurturing Care Framework Domains in Predicting Stunting Among Toddlers: Evidence from the Pagambiran Padang Health Service Area - Amilia, Dian; Putri, Nur Alsyah (Generasi Sains Indonesia, 2024)
A linear growth condition called stunting is brought on by frequent illnesses and poor nutrition. The Nurturing Care Framework, which prioritizes health care, proper nutrition, responsive caregiving, early learning opportunities, and safety and security, is the basis for prevention activities. The purpose of this study was to examine the connection between stunting in toddlers in the Pagambiran Padang Community Health Center region and parental risk factors based on the Nurturing Care Framework. The study was carried out between June 2024 and January 2025 using an analytical cross-sectional design. 214 children between the ages of 24 and 59 months were selected by stratified random sampling and basic random sampling. A questionnaire was used to gather the data, and univariate analysis, bivariate analysis using chi square, and multivariate analysis using multiple logistic regression with the backward technique were all used to examine the results. Stunting was present in 43.9% of people. 55.1 percent of parenting styles were classified as subpar according to the Nurturing Care Framework. Stunting was substantially correlated with safety and security, proper nutrition, and health care, according to multivariate data. The most important factor was enough nutrition. In accordance with the Nurturing Care Framework, the study suggests interdisciplinary cooperation to address nutritional issues, improve basic health services, track children's growth and development, and foster a healthy environment.